Prediction of Synergistic Antibiotic Combinations by Graph Learning - Lv, Ji; Liu, Guixia; Ju, Yuan; Sun, Ying; Guo, Weiying (Frontiers in Pharmacology, 2022)
Antibiotic resistance is a major public health concern. Antibiotic combinations, offering better efficacy at lower doses, are a useful way to handle this problem. However, it is difficult for us to find effective antibiotic combinations in the vast chemical space. Herein, we propose a graph learning framework to predict synergistic antibiotic combinations. In this model, a network proximity method combined with network propagation was used to quantify the relationships of drug pairs and we found that synergistic antibiotic combinations tend to have smaller network proximity. Therefore, network proximity can be used for building affinity matrix. Subsequently, the affinity matrix was fed into a graph regularization model to predict potential synergistic antibiotic combinations. Compared to existing methods, our model shows a better performance in the prediction of synergistic antibiotic combinations and interpretability.